2014
DOI: 10.1073/pnas.1403252111
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8 mediates caspase-1 processing and innate immune defense in response to bacterial blockade of NF-κB and MAPK signaling

Abstract: Toll-like receptor signaling and subsequent activation of NF-κB-and MAPK-dependent genes during infection play an important role in antimicrobial host defense. The YopJ protein of pathogenic Yersinia species inhibits NF-κB and MAPK signaling, resulting in blockade of NF-κB-dependent cytokine production and target cell death. Nevertheless, Yersinia infection induces inflammatory responses in vivo. Moreover, increasing the extent of YopJ-dependent cytotoxicity induced by Yersinia pestis and Yersinia pseudotuberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
253
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(312 citation statements)
references
References 43 publications
22
253
1
5
Order By: Relevance
“…49 Although caspase 1/11 signaling promotes canonical inflammasome signaling, caspase 8 and other members of the ripoptosome complex have also been shown to promote inflammasome activation. [50][51][52][53][54] Our results show that caspase 8 activity was reduced in RIPK1 K45A macrophages, which may limit IL-1β processing in RIPK1 K45A macrophages. We observed that the activity of caspase 8 was reduced in macrophages following infection with ST. Interestingly, caspase 1, which is activated during infection with ST, has been previously shown to limit the processing of various caspases.…”
Section: Ripk1 Interacts With Various Proteins Such As Ciaps Andmentioning
confidence: 66%
See 1 more Smart Citation
“…49 Although caspase 1/11 signaling promotes canonical inflammasome signaling, caspase 8 and other members of the ripoptosome complex have also been shown to promote inflammasome activation. [50][51][52][53][54] Our results show that caspase 8 activity was reduced in RIPK1 K45A macrophages, which may limit IL-1β processing in RIPK1 K45A macrophages. We observed that the activity of caspase 8 was reduced in macrophages following infection with ST. Interestingly, caspase 1, which is activated during infection with ST, has been previously shown to limit the processing of various caspases.…”
Section: Ripk1 Interacts With Various Proteins Such As Ciaps Andmentioning
confidence: 66%
“…9,56 Although RIPK3 is a key component of the necrosome complex, and we have previously shown that RIPK3 is activated following ST infection, 57 RIPK3 has also been shown to promote inflammasome signaling. 11,50,51,53 More recently, MLKL, another member of the necrosome, has also been shown to promote inflammasome signaling, 58 indicating that there is significant overlap in inflammasome and necrosome signaling. We have previously shown that WT and RipK3 − / − mice harbor similar bacterial burden at day 5 postinfection with ST, 57 whereas, in our current study, the bacterial burden in RIPK1…”
Section: Ripk1 Interacts With Various Proteins Such As Ciaps Andmentioning
confidence: 99%
“…However, the role of caspase 8 is complex and context dependent as the causative agent of plague Yersinia pestis and its outer protein YopJ employs caspase 8, RIP1 and RIP3 to trigger cell death and caspase 1 activation. 123,124 Interestingly, another study demonstrated that pharmacological or genetic depletion of the cIAP proteins in macrophages, in conjunction with TLR stimulation, resulted in augmented processing of pro-IL-1b into its mature form. 125 The processing of IL-1b was driven by two independent pathways involving NLRP3/caspase 1 and caspase 8.…”
Section: Rip Kinases and The Inflammasomementioning
confidence: 99%
“…However, Yersinia also inhibits inflammasome activation through the activities of YopK and YopM (36,38,39). Recent studies have revealed that YopJ can cooperate with YopM in activated macrophages to limit inflammasome activation (78,81), although YopJ blockade of NF-B and MAPK signaling triggers the activation of caspase-8 and caspase-1 in naive macrophages (82,83).…”
Section: Discussionmentioning
confidence: 99%